Cooperative learning and traditional teaching modes in physical education - Yang, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study was to apply two methods of cooperative learning including Students Teams Achievement Divisions (STAD) and Teams-Games-Tournament (TGT) into physical education. The study investigated the effect of these 2 learning modes on girls` physical education at junior high school. It was hypothesized that both STAD and TGT learning modes would increase student learning, peer relationships, motivation for achievement and self-esteem compared to traditional teaching. In addition, the study aimed to test if there is any difference in outcomes between the two modes of cooperative learning. Methods Literature review, data collection, and experimental teaching were used in this study. Results The results analyzed by ANOVA indicated the performance of standing long jump increased after the experiment (P<.01), but there was no significant difference among these classes. The difference of performance of solid ball throwing is significant among the classes (F=4.193, P<.05). Multiple comparisons showed that both STAD (Class 2) and TGT (Class 4) were superior to traditional teaching strategies. (Class 6) (P<.01 and P<.05) with respect to improvements in performance. For example throwing performance improved significantly after implementation of the 2 experimental teaching modes. With respect to the cultivation of peer relationships there was a significant positive outcome for the new modes of teaching compared to then traditional mode. In contrast no differences between the groups pre and post test in motivation were demonstrated. Howver those in the STAD group did show improvement. Discussion / Conclusions The results showed that two methods of cooperative learning including STAD and TGT were superior to traditional teaching methods in improving physical fitness, peer relationship, and motivation towards achievement.